Impementasi Kurikulum PAK dan Pendidikan Karakter Terhadap Hasil Belajar Siswa Kelas VII SMP Se-Kecamatan Badiri - Sidauruk, Riados (LPPM-Institut Agama kristen Negeri Tarutung, 2024)
The objectives of this research are 1) to determine the implementation of the PAK curriculum on the learning outcomes of Class VII SMP students in Badiri District; 2) to determine the positive and significant contribution of Character Education to the Learning Outcomes of Class VII Middle School Students in Badiri District; 3) to determine the implementation of the PAK Curriculum and Character Education on the Learning Outcomes of Class VII Middle School Students in Badiri District. The method used in this research is a quantitative research method with inferential statistics. The population is all Class VII Middle School students in Badiri District, 254 people and a sample of 50 people, which is 20% of the total population. Data was collected using a positive closed questionnaire with 34 items. The results of data analysis show that: 1) there is a positive and significant implementation of the PAK Curriculum on the Learning Outcomes of Class VII Middle School Students in Badiri District; 2) there is a positive and significant influence of Character Education on the Learning Outcomes of Class VII Middle School Students in Badiri District; 3) there is a positive and significant influence from the implementation of the PAK Curriculum and Character Education on the Learning Outcomes of Class VII Middle School Students in Badiri District. Proven with the following values: 1) Test the analysis requirements by testing the positive relationship between variables X1 and Y to obtain a value rxy = 0,525; variable X2 with Y obtained value rxy= 0,549; variables X1 and X2 obtain values rxy = 0,425; and between the variables X1 X2 Y, the value ryx1x2 is obtained 0,576 > rtabel (α=0,05, IK: 95%, n=50) = 0,297 Thus it is known that there is a positive relationship between each of these variables. b) Test the significant relationship between variables X1 and Y to obtain a value tcount= 4,270; variable X2 with Y obtained value tcoun = 4,548; and variables X1 and X2 obtain values ttable = 2,549 > ttable (α=0,05, n-2=48) = 2,021 thus it is known that there is a positive relationship between each of these variables. 2) Test the regression coefficient of determination (r2) between variables X1 and Y of 27,52%; variables X2 and Y are equal to 30,11%; and the variables X1 X2 and Y together obtain a determination value of 57,60 % 3) Hypothesis testing using the F test was obtained fcoun > ftable that is 31,917 > 3,23 Thus Ha is accepted and H0 is rejected.